압력용기용 강의 저온 피로크랙 하한계 특성에 관한 연구(Ⅱ) - 박경동(KYUNG-DONG PARK); 김정호(JUNG-HO KIM); 정찬기(CHAN-GI JUNG); 하경준(KYUNG-JUN HA) (Han-guk haeyang gonghak hoeji (Online), 2000)
In this study, CT specimens were prepared from AST SA516 Gr. 70 which was used for pressure vessel plates for room and low temperature service. And we got the following characteristics from fatigue crack growth test carried out in the environment of room and low temperature at 25$^{°}C $, -60$^{°}C $, -80$^{°}C $ and -100$^{°}C $ and in the range of stress ratio of 0.05, 0.3 by means of opening mode displacement. At the constant stress ratio, the threshold stress intensity factor range ${δ} K_{th}$ in the early stage of fatigue crack growth (Region I) and stress intensity factor range $δ $K in the stable of fatigue crack growth (Region II) were increased in proportion to descending temperature. It was assumed that the fatigue resistance characteristics and fracture strength at low temperature is considerable higher than that of room temperature in the early stage and stable of fatigue crack growth region. The straight line slope relation of logarithm da/dN -$δ $K in Region II, that is, the fatigue crack growth exponent m increased with descending temperature at the constant stress ratio. It was assumed that the fatigue crack growth rate da/dN is rapid in proportion to descending temperature in Region II and the cryogenic-brittleness greatly affect a material with decreasing temperature.